Violation of the Contract Contents as A Fraud - Pangarso Wicaksono, Adhiputro (Universitas PGRI Madiun, 2024)
This research aims to analyze the criteria for not fulfilling the agreement which can be categorized as a criminal act of fraud. This research is normative research with a case approach. The source of legal material used is legally and binding verdicts and are analyzed deductively. The results show that something that begins with an agreement and in its implementation there is not fulfilling the agreement can be categorized as a criminal act of fraud (not breach of contract) if the agreement contains elements of fraud. Likewise, if the agreement used as a instrument to get the victim to hand over their goods or something, then if the perpetrator does not fulfilling the agreement, their act can be categorized as a tort or fraud (not a breach of contract), even a tort of fraud was occurred when the victim handed over an item or something belonging to perpretator.